Peran Media pada Keterampilan Membaca Teks Digital di Sekolah Dasar: Tinjauan Literatur Sistematis - Muhammad Insan Muttaqien; Rayindha Melya Arrum (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
Early reading interest in elementary school students is very important to support the achievement of learning. Failure to read means failure to learn various other sciences, so reading skills are the key so that elementary school children are able to learn and develop. A learning media can support a learning process. For this reason, this study wants to examine how the role of media in digital text reading skills in elementary school children. The method used is a systematic literature review. From 172 published articles from various journals, after conducting a screening process using a systematic literature review methodology, 60 articles were selected as the final review. The results of a review of 60 sources found that most of the studies reviewed focused on the role of media in digital text reading skills in elementary schools, followed by general. The results of the role of media on digital text reading skills in elementary schools succeeded in increasing students' interest in learning.